Patterning hypoxic multicellular spheroids in a 3D matrix – a promising method for anti‐tumor drug screening. Issue 1 (22nd December 2015) - Ma, Jingyun; Zhang, Xu; Liu, Yang; Yu, Haibo; Liu, Lianqing; Shi, Yang; Li, Yanfeng; Qin, Jianhua
Abstract: 3D multicellular spheroid models are of great value in the investigation of tumor biology and tumor responses to chemotherapy and radiation. To establish a mimicking tumor microenvironment in vitro, we developed a straightforward method by patterning hypoxic multicellular spheroids in a 3D matrix. The efficacy of this approach was evaluated by characterizing spheroid formation, invasive capability and phenotypic transition in aggressive human glioma cells. We observed enhanced cell proliferation, spheroid formation and invasive capability in U87 glioma cells transfected with hypoxia‐inducible factors (HIFs) compared with non‐treated cells. We also demonstrated that the overexpression of HIFs in hypoxic glioma cells may promote cell migration by epithelial‐mesenchymal transition within the 3D matrix. Compared with conventional 3D culturing techniques, the simple operation, rapid prototyping, low cost and high throughput format of the micro‐patterning method facilitates the characterization of cell proliferation, migration, phenotypic function and drug evaluation in physiologically relevant 3D microenvironments. This in vitro 3D system can recapitulate the physiologically relevant tumor microenvironment and is a promising method for 3D anti‐tumor drug screening and the identification of novel targets for tumor invasion and angiogenesis. Abstract : To establish a mimicking tumor microenvironment in vitro, the authors develop a straightforward method by patterning hypoxic multicellular spheroids in a 3D matrix. This micro‐patterning method facilitates the characterization of cell proliferation, migration, phenotypic function and drug evaluation in physiologically relevant 3D microenvironments.